2013
DOI: 10.6061/clinics/2013(06)26
|View full text |Cite
|
Sign up to set email alerts
|

PROP1 overexpression in corticotrophinomas: evidence for the role of PROP1 in the maintenance of cells committed to corticotrophic differentiation

Abstract: OBJECTIVE:The expression of transcription factors involved in early pituitary development, such as PROP1 and POU1F1, has been detected in pituitary adenoma tissues. In this study, we sought to characterize the transcriptional profiles of PROP1, POU1F1, and TBX19 in functioning and nonfunctioning pituitary adenomas in an attempt to identify their roles in tumorigenesis and hormone hypersecretion.METHODS:RT-qPCR analyses were performed to assess the transcriptional pattern of PROP1, POU1F1, TBX19, and hormone-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
8
0
2
Order By: Relevance
“…The AT motif-binding factor (ATBF1), also known as zinc finger homeobox 3 (ZFHX3), is a crucial cancer suppressor gene. It is worth mentioning that ATBF1 could promote the expression levels of the growth hormone prolactin and TSH-β by binding to the enhancers of POU1F1 (also known as Pit1) and PROP1 (Darling et al, 1998;Qi et al, 2008;Araujo et al, 2013;Yan et al, 2018). These studies showed that the ATBF1 gene was hypothesized to produce important effects on cell differentiation and early development, suggesting that the ATBF1 gene would affect the growth traits in animals.…”
Section: Introductionmentioning
confidence: 99%
“…The AT motif-binding factor (ATBF1), also known as zinc finger homeobox 3 (ZFHX3), is a crucial cancer suppressor gene. It is worth mentioning that ATBF1 could promote the expression levels of the growth hormone prolactin and TSH-β by binding to the enhancers of POU1F1 (also known as Pit1) and PROP1 (Darling et al, 1998;Qi et al, 2008;Araujo et al, 2013;Yan et al, 2018). These studies showed that the ATBF1 gene was hypothesized to produce important effects on cell differentiation and early development, suggesting that the ATBF1 gene would affect the growth traits in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Another transcription factor, Prophet of Pit-1 gene (POMC) encodes a paired-like homeodomain protein and is expressed early in pituitary gland development and regulates cell differentiation (Araujo et al, 2013;Raetzman et al, 2004). Patients with pituitary corticotroph tumors express high levels of PROP1, which leads to increased expression of POMC and ACTH (Araujo et al, 2013).…”
Section: Pituitary Transcription Factorsmentioning
confidence: 99%
“…Furthermore, ATBF1 could promote the expression level of the growth hormone 1 (GH1) gene by binding to the enhancers of the POU1F1 and PROP1 genes (Araujo et al, 2013;Qi et al, 2008), which are the key genes in mammalian growth, development and the lactationrelated hypothalamic-pituitary-adrenal (HPA) axis pathway (PITX2/PITX1 -HESX1 -LHX3/LHX4 -PROP1 -POU1F1) (Davis et al, 2010;Ma et al, 2017). In addition, another key gene in the HPA axis pathway, PITX2, has a positive regulation relationship with ATBF1 under the participation of miR-1 (Huang et al, 2015).…”
mentioning
confidence: 99%